INTERACTION BETWEEN DISLOCATION AND TWO CIRCULAR CYLINDRICAL INCLUSIONS - 吴林志 杜善义 谭兴达 (Acta mechanica Sinica, 1998)
In this paper,the elastic field of the infinite homogeneous mediumwith two circular cylindrical inclusions under the action of a screw dislocation is in-vestigated and the corresponding analytical solution is obtained.Here,the conformalmapping and the theorem of analytical continuation are used.From the results ob-tained,it can be seen that the elastic field depends on the shear moduli of individualphases,the geometric parameters of the system,and the position and relative slip ofthe screw dislocation.In addition,the corresponding specific cases are also consid-ered in this paper when two circular cylindrical inclusions are tangent to each otherand they are holes and/or rigid inclusions.Finally,numerical results are illustratedto show the interaction between the screw dislocation and two circular cylindricalinclusions.